Acetylation of HMGB1 by JNK1 Signaling Promotes LPS-Induced Peritoneal Mesothelial Cells Apoptosis. (12th November 2018) - Cao, Shirong; Li, Shu; Wang, Yating; Shen, Jiani; Zhou, Yi; Li, Huiyan; Yu, Xueqing; Mao, Haiping
Abstract : Increased high mobility group box 1 (HMGB1) in dialysis effluence is associated with the presence of peritoneal dialysis-related peritonitis in patients and peritoneal dysfunction in acute peritonitis mice model, but it remains unclear whether HMGB1 is involved in peritoneal mesothelial cell injury and functions via molecular posttranslational modifications by acetylation in this process. Here we first showed correlation between HMGB1 acetylation level in dialysis effluence of patients and occurrence of Gram-negative peritonitis. The increased level of acetylated HMGB1 was similarly observed under the lipopolysaccharides (LPS) treatment in both human peritoneal mesothelial cell line (HMrSV5) and mice visceral peritoneum tissue. Overexpression of wild-type, but not hypoacetylation mutant of HMGB1, enhanced LPS-induced apoptosis in HMrSV5 cells, which was accompanied by elevated protein levels of BAX and cleaved-caspase 3 compared to the control. Pretreatment of HMrSV5 cell with JNK inhibitor attenuated LPS-induced HMGB1 acetylation. Consistently, primary peritoneal mesothelial cells from Jnk1 -/- mice showed a lower protein contents of acetylated HMGB1, fewer apoptosis, and decreased protein expression of BAX and cleaved-caspase3 after LPS exposure, as compared to those from wild-type mice. In conclusion, our data demonstrated HMGB1 promotes LPS-induced peritoneal mesothelial cells apoptosis, which is associated with JNK1-mediated upregulation of HMGB1 acetylation.